The effectiveness of Liliaceae phyllospheric Actinomycetes as biocontrol agent of purple blotch disease (Alternaria porri Ell. Cif) on shallot - Wati, Cheppy; Nawangsih, Abdjad Asih; Wahyudi, Aris Tri; Wiyono, Suryo; Munif, Abdul (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Purple blotch, caused by Alternaria porri, affects leaves and tubers, leading to reduced yields. Traditionally, synthetic chemical fungicides were heavily relied upon for control. As an alternative, biocontrol agents like actinomycetes have gained attention. Some actinomycetes can suppress plant pathogens by producing antifungal compounds. This research aimed to investigate the efficacy of phyllosphere actinomycetes from Liliaceae plants as biocontrol agents against purple blotch disease on shallots in the greenhouse. Conducted at the IPB University Plant Bacteriology and Mycology Laboratory and the greenhouse at Bogor Agricultural Development Polytechnic, West Java, the research involved several stages, including pathogen identification, preparation of actinomyces inoculum and A. porri, and application of actinomycetes biocontrol agents to shallots in the greenhouse. A. porri isolates were obtained from shallot production centers in the Brebes area, Central Java. The use of the actinomycetes from the phyllosphere effectively suppressed purple blotch disease, with the lowest area under the disease development curve (AUDPC) recorded at 635.9% for the CFS28 isolate. Lower AUDPC values indicated slower disease progression. Actinomycetes biocontrol agents showed promising efficacy, with the CFS28 isolate achieving the highest efficacy percentage of 78.37%. Additionally, plant growth was significantly enhanced by actinomycete application, with tuber sizes ranging from 1.44 to 2.06 g, fresh weights from 17.63 to 24.72 g, and dry weights of shallot bulbs from 5.43 to 17.96 g. The incubation period for A. porri could be extended by actinomycetes, ranging from 5.43 to 8.5 days for purple blotch symptoms to manifest on shallots. The use of Actinomyces phyllosphere biocontrol agents holds promise for disease control on other plants’ leaves, contributing to environmentally friendly and sustainable agricultural practices.